Industrial source discharge estimation for pharmaceutical and personal care products in China. (25th December 2022) - Wang, Rui; Lu, Yonglong; Song, Shuai; Yang, Shengjie; Wu, Yanqi; Cui, Haotian
Abstract: Long-term exposure to water contaminated with pharmaceutical and personal care products (PPCPs) can cause potential harm to humans and ecosystems. Industrial manufacturing discharge is the source for PPCPs emission into natural water. Since industrial source discharge inventories and environmental fate information of PPCPs are lacking in China, a fast low-cost estimation method of PPCPs industrial source discharge is proposed in this paper. The estimated results are fitting well with the existing field monitoring data, and shows that China's highly industrialized eastern provinces have significantly higher discharge intensity than western and northern provinces. This study provides a valuable approach for rapid response to PPCPs emergency. Graphical abstract: Image 1 Highlights: The method for PPCP industrial source discharge estimation is improved in terms of time and capital cost. Production source emission factors for PPCPs are calculated. The total discharge from typical PPCP production sources in coastal regions was 227.66 tons in 2019. Production source discharges of typical PPCPs were highest for caffeine and lowest for chlortetracycline.